2021
DOI: 10.1111/febs.16316
|View full text |Cite
|
Sign up to set email alerts
|

Role of non‐enzymatic chemical reactions in 3‐methylglutaconic aciduria

Abstract: 3‐Methylglutaconic (3MGC) aciduria occurs in numerous inborn errors associated with compromised mitochondrial energy metabolism. In these disorders, 3MGC CoA is produced de novo from acetyl CoA in three steps with the final reaction catalysed by 3MGC CoA hydratase (AUH). In in vitro assays, whereas recombinant AUH dehydrated 3‐hydroxy‐3‐methylglutaryl (HMG) CoA to 3MGC CoA, free CoA was also produced. Although HMG CoA is known to undergo non‐enzymatic intramolecular cyclisation, forming HMG anhydride and free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Previous studies investigating AUH activity employed Tris as the buffering agent [ 9 , 10 , 11 , 12 ]. However, knowledge that trans -3MGC CoA is susceptible to isomerization/cyclic anhydride formation suggests that cis -3MGC anhydride may react with the free amino group on Tris to yield 3MGCylated Tris as a product and, thereby, attenuate 3MGCylated BSA signal intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies investigating AUH activity employed Tris as the buffering agent [ 9 , 10 , 11 , 12 ]. However, knowledge that trans -3MGC CoA is susceptible to isomerization/cyclic anhydride formation suggests that cis -3MGC anhydride may react with the free amino group on Tris to yield 3MGCylated Tris as a product and, thereby, attenuate 3MGCylated BSA signal intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, individuals with psoriasis should limit their intake of ultra-processed foods to prevent the potential risk increase associated with high levels of catechol sulfate metabolites. Dysregulation of 3-methylglutaconic acid metabolism has been noted in conditions such as 3-methylglutaconic aciduria and various congenital metabolic defects where mitochondrial energy metabolism is impaired ( 44 , 45 ). Elevated levels of 3-methylglutaconic acid detected in various inherited metabolic diseases could lead to dysfunctions in the nervous system, heart, liver, and other organs ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting cyclic anhydride is reactive and can be hydrolyzed to yield the dead-end organic acid, cis -3MGC acid, or it can undergo nucleophilic attack by protein lysine side chain amino groups to form a covalent adduct ( Figure 4 ). Based on this non-enzymatic reaction sequence, a potential route from trans -3MGC CoA to cis -3MGC acid exists [ 22 ]. Not only does this reaction sequence provide an explanation for the presence of cis -3MGC acid in urine of subjects with primary and secondary 3MGC aciduria, it also explains how AUH’s equilibrium constant [ 16 ], which strongly favors hydration over dehydration, is overcome.…”
Section: A Non-enzymatic Reaction Sequence Converts Trans ...mentioning
confidence: 99%
“…The hydrolysis of cis -3MGC anhydride exclusively generates cis -3MGC acid, thereby providing a molecular explanation for the occurrence of cis -3MGC acid in urine of subjects with 3MGC aciduria. In the case of protein 3MGCylation, in vitro studies [ 22 ] revealed that, although cis -3MGC anhydride displays a preference for hydrolytic cleavage versus acylation, considerable protein 3MGCylation also occurs. The fact that Young et al [ 17 ] detected 3MGCylated bovine serum albumin (BSA) following incubation of trans -3MGC CoA with BSA provides compelling evidence in support of the non-enzymatic phase of the acetyl CoA diversion pathway.…”
Section: A Non-enzymatic Reaction Sequence Converts Trans ...mentioning
confidence: 99%
See 1 more Smart Citation